Sistem Informasi Pembelajaran Taman Pendidikan Al-Qur’an di Yayasan Al-Muttaqien Jadid (TPQ) - Rasiban; Hanif, Zuhdi; Sumabrata, Raden Muhammad Jachfitrah Ardhi; Yuliansyah, Ahmad Fauzan (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
This research aims to determine the TPA academic system currently running at Al-Muttaqien Jadid. This research is descriptive research using qualitative methods. Data collection was carried out by interviews, observation and documentation, as well as using literature studies from various sources related to the questions asked in the research. It was found that there was a problem with the TPA Academic system, including regarding student registration, class division and scheduling, which still uses the bookkeeping method, it is difficult to get information regarding student data, class data, teacher data and subject data. Apart from that, the process of class division and scheduling cannot be completed quickly due to difficulties in finding data, the number of students being placed in excess of the quota often occurs, so mistakes or mistakes often occur in recording students' grades. So that registration, payment and distribution data can be processed quickly and accurately, a web-based application is needed. By implementing this application, it can help academic processing in preparing payment reports and student registration so that the management of TKA-TPA in the data collection process makes coordination and coaching easier. From the research results, it can be concluded that registration, payment, class division and scheduling using the bookkeeping method requires quite a long time in processing data and storing data.